Diagnosing meridional amblyopia in astigmats on the basis of assessment of asymmetries in visual acuity and refraction as vector quantities (Ukrainian Journal of Ophthalmology, 2025)
Background: Asymmetry in refraction may cause meridional amblyopia and impairments in the mechanisms underlying binocular vision in patients with astigmatism. There have been contradictory reports on the features and incidence of meridional amblyopia in patients with astigmatism. These contradictions have been attributed to the fact that the studies vary in methodologies and criteria used for visual acuity assessment.Purpose: To improve the algorithm for diagnosing meridional amblyopia in patients with hyperopic astigmatism on the basis of assessment of asymmetries in meridional separable visual acuity and refraction as vector quantities.Material and Methods: Ninety three patients aged 6 to 12 years, with both refractive amblyopia and compound with-the-rule hyperopic astigmatism were included in the study, and underwent examination. The sphercal component of refraction ranged from 0.5D to 1.75D, and the astigmatic component of refraction, from 0.75D to 2.0D. Best-corrected visual acuity was assessed using letters and Landolt rings of Shevalev Chart and digits generated by a Hoya chart projector. Visual acuity characteristics were determined for the amblyopic eye, fellow eye and binocularly. Meridional separable visual acuity was measured with Landolt rings with the help of specially developed software. Optotypes were presented on the computer screen at a 5-m distance. Threshold meridional separable visual acuity was measured in the meridians corresponding to principal astigmatism axes under gradual change (with an increment of ±7.0 arc second) in the angular size of the optotype. Tests were presented monocularly and binocularly on a 15-inch 1600×1200-resolution display.Results: Graphic comparison of the results of visual acuity measurements using optotypes of different shapes in amblyopes with similar type of astigmatism demonstrated that, in the groups of patients with the same letter visual acuity, Landolt visual acuities can be higher, lower or equal to letter visual acuities. Of the study patients, 42.5% were found to have no meridional amblyopia, and 57.5%, to have meridional amblyopia, as assessed using Landolt rings. Particularly, 35% and 22.5% of the study patients had visual acuity in the horizontal meridian better and worse, respectively, than in the vertical meridian.Conclusion: Meridional separable visual acuities in patients with both amblyopia and similar type of hyperopic astigmatism are vector quantities and may vary in orthogonal retinal meridians not only in the magnitude, but also in the sign. Meridional visual acuity studies will allow a diagnosis of meridional amblyopia to be clarified not only based on the presence of asymmetry in visual acuity in orthogonal retinal meridians, but also based on the direction of asymmetry in visual acuity with respect to the principal astigmatic refraction meridians.
Keywords: astigmatism; visual acuity; individual variations; meridional visual acuity; meridional amblyopia